Aplikasi Pengenalan Senjata Tradisional Yogyakarta Berbasis Augmented reality - Satria, Fajar; Waluyo, Anita Fira (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Yogyakarta, a city of culture, has a variety of cultures, including traditional weapons, but these are currently difficult to find. Research has shown that Augmented reality technology can educate the public about the culture of a region, such as the introduction of traditional Yogyakarta weapons through an application that displays 3D objects of traditional Yogyakarta weapons. By utilizing Augmented reality technology in the introduction of traditional Yogyakarta weapons, it becomes a material that is interesting to learn. This application can display 3D objects of traditional Yogyakarta weapons, so that the public can visualize traditional weapons that are currently quite difficult to find. The 3D objects were made based on data from a book published by the Ministry of Education and Culture. The target marker is made in the form of a QR code with a photo of a weapon in the middle, when the marker is detected, a 3D object will appear above it. The results of the testing showed that all features were able to run well.